Caregiver role development in chronic disease: A qualitative study of informal caregiving for veterans with diabetes. (March 2022) - Fields, Beth; Makaroun, Lena; Rodriguez, Keri L; Robinson, Claire; Forman, Jane; Rosland, Ann-Marie
Objective: Support for chronic conditions such as diabetes from friends and family positively influences health management and outcomes, but limited data exist on how and why caregivers assume specific support roles for otherwise independent aging adults. We conducted a qualitative study to examine the nature of caregivers' roles in supporting Veterans' management of a chronic condition and caregivers' reasons for assuming those roles, using Type 2 diabetes as an example. Methods: Thirty-two interviews were conducted with Veterans with Type 2 diabetes (n = 20) and their caregivers (n = 12). Two coders independently analyzed interview transcripts using a thematic analysis approach. Results: Three central roles of caregivers in diabetes management were described: direct care support, memory support/care organizer, and advocate. Three explanations for assuming caregiving roles emerged: changes in patient health, natural evolution of family roles, and caregivers' health care experience or training. Discussion: Understanding what roles caregivers fill and why is critical to designing services to support caregivers in helping improve chronic health condition management for aging adults.